Use of Gamification in the IB History Class and as a Tool for Form Teacher. New Empirical Research and Solutions - Janiec, Jerzy (Kultura-Społeczeństwo-Edukacja, 2015)
This article is a presentation of new empirical research and solutions for educators who tend to examine new methods and philosophies designed for improving teaching-learning process around the world. For that purpose, the author is introducing reader to the International Baccalaureate (IB) three-dimenstional way of creating school’s curriculum with concept-based approach and idea to transfer knowledge between disciplines using global, key and related concepts. Accomplishment of this work provides a chance to form solutions according to each school’s ‘wants and needs’, e.g. focusing on stimulation of pupils behaviour by implementing the Point System of Behavioral Assessment like in the IB World School No. 006654 case. And then teachers are able to standardize new teaching methods, such as gamification, successfully implementing them in their classes. What’s more gamification can be easily used as a tool for form teachers in order to improve pupils’ social skills and strengthening their involvement in a lesson.